Novel rotor design of dual‐stator brushless doubly fed generator based on surrogate model - Hao Wang; Yue Zhang; Shi Jin; Huijun Wang; Fengge Zhang (IET Renewable Power Generation, 2021)
Abstract Dual‐stator brushless doubly fed generator (DSBDFG) is a novel generator applied for wind power generation, and the electromechanical energy conversion between the stator and rotor is realised by the magnetic field modulation of the special rotor structure. Therefore, the rotor design is critical to improve the performance of DSBDFG. In this study, the different rotor structures are compared and analysed, and the position of the non‐magnetic ring is determined. In order to reduce the computational cost and improve the optimisation efficiency, the surrogate model coupled with the multi‐island geometric algorithm is applied for the optimisation of the magnetic barrier layer of the cage barrier rotor. In addition, in order to reduce the effect of skin effect on the copper loss of cage bars of the rotor, the different simulation models, whose cage bars have different layer number, are simulated and analysed. Finally, the simulation and experimental results verify the correctness of the theoretical analysis and the effectiveness of surrogate model used for the rotor optimisation design of DSBDFG.